2019
DOI: 10.1186/s12889-019-7909-4
|View full text |Cite
|
Sign up to set email alerts
|

Cluster-randomised trial evaluating a complex intervention to improve mental health and well-being of employees working in hospital – a protocol for the SEEGEN trial

Abstract: BackgroundHealth care employees in Germany and worldwide are exposed to a variety of stressors. However, most of the hospitals in Germany lack a systematic workplace health management. Thus, this study aims at the evaluation of the effects of a behavioural as well as organisational (´complex´) intervention on the mental health and well-being of hospital staff.MethodsMental health in the hospital workplace (SEElische GEsundheit am Arbeitsplatz KrankeNhaus – SEEGEN) is an unblinded, multi-centred cluster-randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 42 publications
0
43
0
2
Order By: Relevance
“…Thus, increasing the likelihood of making medical errors that may increase the risk to patients. Moreover, it has been demonstrated that acute stress in disasters could result in a lasting effect on the overall well-being [50]. Therefore, looking after the mental health of healthcare workers during the COVID-19 pandemic should be a crucial public health concern.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, increasing the likelihood of making medical errors that may increase the risk to patients. Moreover, it has been demonstrated that acute stress in disasters could result in a lasting effect on the overall well-being [50]. Therefore, looking after the mental health of healthcare workers during the COVID-19 pandemic should be a crucial public health concern.…”
Section: Discussionmentioning
confidence: 99%
“…The interview study was embedded in the cluster-randomized collaborative study "Mental Health in the workplace hospital" (SEEGEN), which aims to develop and implement behavioral and relational interventions to reduce stress in hospitals (Mulfinger et al, 2019). This project was funded by the German Federal Ministry of Education, and Research (BMBF), The University of Duisburg-Essen, Heinrich-Heine University Düsseldorf, Universities of Ulm, Tübingen, and Heidelberg are affiliated partners.…”
Section: Author's Notementioning
confidence: 99%
“…There was also error correlation between item 30 and 31 in the modi ed model. Interpersonal relationship may lead to bene ts in subjective well-being and performance [38]. Therefore, there are interacting effects between satisfaction with interpersonal relationships and performance in life, work or study (Item 30: Are you satis ed with your interpersonal relationship in society?…”
Section: Discussionmentioning
confidence: 99%